Pathway Association Studies Reveal Gene Loci and Pathway Networks that Associated With Plasma Cystatin C Levels - Jiao, Hongxiao; Zhang, Miaomiao; Zhang, Yuan; Wang, Yaogang; Li, Wei-Dong (Frontiers in Genetics, 2021)
As a marker for glomerular filtration, plasma cystatin C level is used to evaluate kidney function. To decipher genetic factors that control the plasma cystatin C level, we performed genome-wide association and pathway association studies using UK Biobank data. One hundred fifteen loci yielded P values less than 1×10-100, three genes (clusters) showed the most significant associations, including the CST8-CST9 cluster on chromosome 20, the SH2B3-ATXN2 gene region on chromosome 12, and the SHROOM3-CCDC158 gene region on chromosome 4. In pathway association studies, forty significant pathways had FDR (false discovery rate) and or FWER (family-wise error rate) ≤ 0.001: spermatogenesis, leukocyte trans-endothelial migration, cell adhesion, glycoprotein, membrane lipid, steroid metabolic process, and insulin signaling pathways were among the most significant pathways that associated with the plasma cystatin C levels. We also performed GWAS for eGFR, top associated genes were largely overlapped with those for cystatin C.